On the spectrum and string tension of U(1) lattice gauge theory in 2+1 dimensions - Athenodorou, A; Teper, M (Springer Verlag, 2019)
We calculate the low-lying spectra of glueballs and confining flux tubes in the U(1) lattice gauge theory in 2 + 1 dimensions. We see that up to modest lattice spacing corrections, the glueball states are consistent with being multiparticle states composed of non-interacting massive JPC = 0− − particles. We observe that the ag2 → 0 limit is, as expected, unconventional, and follows the well-known saddle-point analysis of Polyakov to a good approximation. The spectrum of closed (winding) flux tubes exhibits the presence of a massive world-sheet excitation whose mass is consistent with that of the bulk screening mass. These U(1) calculations are intended to complement existing lattice calculations of the properties of SU(N ≥ 2) and SO(N ≥ 3) gauge theories in D = 2 + 1.